THEO-PROPHETIC JURISPRUDENCE: TRACING THE GENEALOGY OF THE ISLAMIC LAW’S FORMATION AND GROWTH IN RASULULLAH ERA - Kholish, Moh Anas; Galib, Andi Muhammad (Arena Hukum, 2023)
This paper concisely and analytically presents the history of tasyri', or the formation of Islamic law in the Prophet's era. By using the term "Theo-Prophetic Jurisprudence," this paper also provide a response and rebuttal to the view that Islamic law is a product of Muhammad's jurisprudence. The results of this qualitative research with conceptual and historical approaches indicate that the formation of Islamic law began in the prophetic period. The period of the formation of Islamic law or the Prophet Muhammad's jurisprudence is divided into two phases, namely the Mecca phases which includes everything related to belief, morals-ethics, and fiqh (law); and the Medina phase which is more oriented to the formation of law, including social situations or the social construction phase. Islamic law or the Prophet Muhammad's jurisprudence is not a product of Muhammad's ideology like some scholars view that Islamic law does not have theological and juristic nuances but only historical-sociological aspects.